Research on Fuel Economy of Hydro-Mechanical Continuously Variable Transmission Rotary-Tilling Tractor - Mingzhu Zhang; Ningning Wang; Sikang Zhou (Energies)
In response to the absence of an effective variable speed control strategy for tractors equipped with hydro-mechanical continuously variable transmission (HMCVT) during rotary-tillage operations, this study investigates the power transfer and fuel economy characteristics of the rotary-tilling tractor during operation. A dynamic analysis of the rotary-tilling tractor is conducted, and a dynamic model for the rotary-tilling tractor is developed. This model comprehensively incorporates factors such as the transmission efficiency of the HMCVT, the horizontal cutting force of the rotary tillage, and the torque coupling relationships between the various transmission subsystems and utilizes a backward modeling approach with dual inputs: walking load and rotary-tillage load. Based on the measured data of the effective fuel consumption rate from 64 engine groups within the study, a BP neural network model of the engine’s fuel characteristics is developed. Furthermore, it is proposed that fuel consumption per kilometer of rotary-tillage operation be used to characterize the fuel economy of the rotary-tilling tractor. The results demonstrate that the increase in forward speed concurrently enhances both the productivity and fuel economy of the rotary-tilling tractor. This finding provides a theoretical foundation for developing a variable speed control strategy for the rotary-tilling tractor.